Is the Common Core racing America to the top? Tracking changes in state standards, school practices, and student achievement - Lee, Jaekyung; Wu, Yin (Education Policy Analysis Archives, 2017)
This study examines the trends of the U.S. states’ reading and math proficiency standards before and after the adoption of the Common Core State Standards (CCSS) and explores their impact on school practices and student achievement. Drawing on the 2003-15 National Assessment of Educational Progress (NAEP) grades 4 and 8 assessment and survey datasets, the study gives new insights into the CCSS policy challenges and outcomes. The states that adopted CCSS raised the rigor of proficiency standards for their student assessments, reversing ‘race to the bottom’ trend during the earlier period of the No Child Left Behind Act (NCLB). However, the CCSS states failed to improve schools’ alignment of ELA and math programs with state/district assessments and also failed to improve students’ reading and math achievement more than the non-CCSS counterparts. The Common Core has helped America race to the top for performance standards, but not for performance outcomes yet.